Identification of Lifeboat Maintenance Issues on KM. Egon in Support of Maritime Safety - Joan Krisna Reyhanandi; Sari, Dian Kurnianing; Indriyani, Kristin Anita (Politeknik Ilmu Pelayaran Semarang, 2025)
Lifeboats are the main safety equipment on ships that require periodic maintenance according to SOLAS standards to ensure preparedness in an emergency. However, the observation results on KM. Egon shows the condition of damaged vital components and the lack of crew readiness in their use. The purpose of this study is to identify the factors that affect lifeboat maintenance on KM. Egon, analyze its impact, and formulate efforts to optimize lifeboat readiness. This research uses descriptive qualitative methods with data collection techniques through observation, interviews, and documentation. Data analysis was carried out using the fishbone diagram method. The results showed that lifeboat maintenance on KM. Egon is influenced by maintenance methods that are not in accordance with SOPs, low crew understanding, and busy cruise schedules. The impacts that arise include component damage, decreased lifeboat readiness, and non-routine training. It was concluded that the optimization of lifeboat maintenance on KM. Egon is influenced by method, human, material, environment, and machine factors. Therefore, it is recommended to increase crew understanding through routine training and safety meetings, proactive provision of spare parts by the company, and maximize maintenance when the ship is sailing. In addition, ship officers need to more actively monitor and evaluate the condition of safety equipment.